Corn straw cellulose co-polyacrylamide and acrylic acid hydrogel adsorption material as well as preparation method and application thereof

By using hydrogel adsorption materials prepared by copolymerizing corn straw cellulose with acrylic acid and acrylamide, the problems of low resource utilization and great negative environmental impact in heavy metal pollution treatment are solved, and efficient and environmentally friendly heavy metal ion adsorption and removal effects are achieved. .

CN119215863APending Publication Date: 2024-12-31HUNAN UNIV
View PDF 0 Cites 8 Cited by

Patent Information

Application Number
CN202411437553.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The prior art has problems with low resource utilization and great negative environmental impact in dealing with heavy metal pollution, and it is difficult to effectively remove heavy metal ions in water bodies.

Method used

Using corn straw cellulose as the skeleton, hydrogel adsorption materials with three-dimensional porous structures are prepared by copolymerization with acrylic acid and acrylamide. The excellent ion adsorption capacity significantly reduces heavy metal pollution and improves agricultural waste. Resource utilization rate.

Benefits of technology

The hydrogel material exhibits efficient heavy metal ion adsorption performance, with a maximum adsorption amount of 434.8 mg/g, 277.7 mg/g and 261.8 mg/g, which has high selectivity for lead, cadmium and copper ions, and it is 6 times The adsorption performance after circulation is almost not significantly affected, reducing the environmental negative impact of the wastewater treatment process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119215863A_ABST
    Figure CN119215863A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of adsorption materials, and discloses a preparation method and application of a hydrogel adsorption material prepared by copolymerizing cellulose with acrylic acid and acrylamide. The method comprises the following steps: extracting cellulose from corn straws; placing cellulose in a sodium hydroxide / urea / water system, stirring and dissolving; the preparation method comprises the following steps: uniformly mixing acrylamide and acrylic acid in water to prepare a modified solution; sequentially adding the modified solution, N, N '-methylene bisacrylamide and potassium persulfate into the cellulose solution, and stirring and mixing; putting the mixed solution into a drying oven for gelation to obtain the cellulose co-polyacrylamide and acrylic acid hydrogel adsorption material. A large number of groups such as hydroxyl and carboxyl are introduced to the surface of the hydrogel adsorption material prepared by the method, the adsorption capacities of heavy metals such as lead, cadmium and copper reach 434.8 mg / g, 277.7 mg / g and 261.8 mg / g respectively, and heavy metal ions in a water body can be effectively and quickly removed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adsorption and removal of heavy metals in environmental water bodies, and specifically relates to a corn straw cellulose copolymer polyacrylamide and acrylic acid hydrogel adsorption material and a preparation method and application thereof. Background Art

[0002] With the rapid advancement of industrialization, the problem of heavy metal pollution in aquatic ecosystems is becoming increasingly serious. Heavy metal ions, such as cadmium, lead, copper, etc., pose a serious challenge to environmental safety. Due to their high toxicity and persistence, these heavy metals are more likely to accumulate in ecosystems for a long time compared to organic pollutants, and can pose a threat to human health even at trace concentrations. Traditional methods for removing heavy metal ions mainly include chemical precipitation, ion exchange, chemical oxidation / reduction, reverse osmosis, electrodialysis and adsorption. Among these methods, adsorption technology has become the preferred solution for treating heavy metal pollution due to its advantages such as simple operation, high cost-effectiveness, environmental friendliness and reusability.

[0003] As an efficient adsorption material, hydrogels have shown great application potential in the field of wastewater treatment. These materials usually have a three-dimensional cross-linked network structure, which can be formed by physical or chemical cross-linking between polymer chains. The ease of operation, renewability and biodegradability of hydrogels make them an ideal choice for heavy metal ion treatment. In particular, natural materials, such as cellulose, are gradually replacing synthetic materials and becoming the preferred raw material for hydrogel production due to their abundant sources, excellent biodegradability and diverse functional groups. While effectively removing heavy metal impurities, hydrogels can also avoid secondary environmental pollution caused by adsorption materials. Their key role in environmental governance is self-evident. At a time when resources are becoming increasingly scarce and the utilization rate of waste resources is low, the development of polymer materials based on natural biomass is of vital importance to promoting sustainable development. Summary of the invention

[0004] Therefore, in view of the limitations of the existing technology in dealing with heavy metal pollution, the present invention aims to propose an innovative solution, namely a copolymerized polyacrylamide and acrylic acid hydrogel adsorption material based on corn straw cellulose, together with its preparation method and application technology. The hydrogel adsorption material prepared by the method described in the present invention exhibits excellent ion adsorption capacity, which is not only expected to significantly reduce the pollution of heavy metals to the environment, but also to improve the resource utilization rate of agricultural waste. While reducing the negative impact on the environment during wastewater treatment, the present invention also provides an effective strategy for the protection of the natural environment. The purpose of the present invention is achieved by adopting the following technical scheme, and the steps are as follows.

[0005] (1) The corn stalks are pretreated by firstly boiling them in a sodium hydroxide solution and then bleaching them in a sodium hypochlorite solution. After the treatment, pure corn stalk cellulose is obtained through filtering, washing and drying steps.

[0006] (2) The pretreated corn stover cellulose is dissolved in a sodium hydroxide / urea / water (alkaline urea) system to form a translucent cellulose solution, namely, reaction system 1.

[0007] (3) mixing acrylic acid and acrylamide in water to form a uniform modified solution, i.e., reaction system 2;

[0008] (4) The reaction system 2 is slowly added to the reaction system 1 and stirred thoroughly to ensure uniform mixing. Then, N,N'-methylenebisacrylamide is added as a crosslinking agent and potassium persulfate is added as an initiator.

[0009] (5) heating the mixed solution obtained in step (4) in an oven to promote a gelation reaction, thereby forming a hydrogel;

[0010] (6) The hydrogel obtained in step (5) is thoroughly washed to remove unreacted monomers. Finally, the hydrogel is placed in an oven for drying to obtain a final hydrogel adsorption material product, which is then dried and stored.

[0011] In the above steps, it is further improved that the pretreatment in step (1) includes washing, drying and crushing in sequence. In the present invention, the washing agent is preferably water, and the number of washing times is based on effectively removing impurities on the surface of the corn stalks. The drying temperature is preferably 60°C, and the time is not limited, and drying is sufficient. The crushing speed is preferably 30000r / min, and the time is preferably 30s. The mass volume ratio of the corn stalks to the sodium hydroxide solution and the sodium hypochlorite solution is 1: (15-20), the mass fractions of the sodium hydroxide and sodium hypochlorite aqueous solutions are both 5-15%, the heating temperature is 50-70°C, and the heating time is 2-3h.

[0012] In the above steps, it is further improved that the mass ratio of sodium hydroxide / urea / water in step (2) is (5-7):(12-15):(78-83).

[0013] In the above steps, the method for dissolving the corn straw cellulose in the alkaline urea solution in step (2) is further improved as follows: placing the sodium hydroxide / urea / water solution in a 0°C ice water bath, weighing 0.5-1.5g of corn straw cellulose and dispersing it in the alkaline urea solution, and rapidly stirring at a speed of 600-800r / min for 30-40min to obtain a translucent cellulose solution.

[0014] In the above steps, it is further improved that in step (3), the mass ratio of acrylic acid to corn straw cellulose is 0.5-1:1, and the mass ratio of acrylamide to corn straw cellulose is 1-2:1.

[0015] In the above steps, it is further improved that in step (4), the volume ratio of reaction system 1 to reaction system 2 is 1 to 5:1.

[0016] In the above steps, it is further improved that in step (4), the molar amount of the crosslinking agent is 1-2% of the molar amount of the total monomers (acrylic acid and acrylamide), and the molar amount of the initiator is 0.5-1% of the molar amount of the total monomers.

[0017] In the above steps, it is further improved that the heating temperature in step (5) is 50-60° C. and the heating time is 2-3 h.

[0018] In the above steps, it is further improved that the drying temperature in step (6) is 60-70° C., and the drying time is not limited until the hydrogel reaches a constant weight.

[0019] The purpose of the present invention can also be achieved by the following technical solutions. According to the present invention, a corn straw cellulose copolymerized with polyacrylamide and acrylic acid hydrogel adsorption material is provided, which is characterized by having a three-dimensional porous structure and excellent water absorption and swelling performance, with a swelling ratio of up to 170.4. The adsorption material contains hydroxyl (-OH), carboxyl (-COOH), carbonyl (C=O) and carbon-nitrogen bond (CN), and has good water absorption and swelling performance. 2+ ), cadmium (Cd 2+ ), copper (Cu 2+ ) ions showed significant adsorption capacity, and the maximum adsorption amounts were 434.8 mg / g, 277.7 mg / g, and 261.8 mg / g, respectively. The hydrogel was prepared by the above method.

[0020] The purpose of the present invention can also be achieved by adopting the following technical scheme. According to the present invention, there is provided an application of the above-mentioned corn straw cellulose copolymer polyacrylamide acrylic acid hydrogel in the adsorption of heavy metal ions.

[0021] Preferably, in the application of the corn straw cellulose copolymerized with polyacrylamide and acrylic acid hydrogel in the adsorption of heavy metal ions, the heavy metal ions are Pb 2+ 、Cd 2+ , Cu 2+ .

[0022] The hydrogel of the invention uses corn straw cellulose as a skeleton, thereby increasing the overall mechanical strength and compression resistance; at the same time, acrylamide and acrylic acid are used as monomers, thereby providing sites for the adsorption of heavy metal ions; the obtained corn straw cellulose copolymerized with polyacrylamide and acrylic acid hydrogel contains a large number of hydroxyl groups and carboxyl groups, has a three-dimensional porous structure, has strong adsorption performance for heavy metal ions, has high selectivity for lead, does not cause secondary pollution to water bodies, is easy to prepare and can be recycled, and has broad application prospects in actual wastewater treatment.

[0023] Furthermore, corn straw cellulose is extracted from corn straw, which realizes the reuse of waste resources, reduces costs, and achieves the effect of "treating waste with waste."

[0024] The corn straw cellulose copolymerized with polyacrylamide acrylic acid hydrogel prepared by the above steps has a three-dimensional porous structure, good water absorption and swelling performance, a swelling ratio of 170.4, and contains hydroxyl (-OH), carboxyl (-COOH), carbonyl (C=O), and carbon-nitrogen bond (CN). 2+ 、Cd 2+ , Cu 2+ The maximum adsorption capacity of Pb was 434.8 mg / g, 277.7 mg / g, and 261.8 mg / g, respectively. After 6 cycles, the developed adsorption material showed good cycle stability, and its adsorption performance was hardly affected significantly. The specific results showed that after the sixth cycle, Pb 2+ The adsorption capacity of Cd decreased from 445 mg / g to 410 mg / g. 2+ The adsorption capacity of Cu 2+ The adsorption capacity of the material slightly decreased from 150 mg / g to 135 mg / g. The above data show that the material still maintains about 90% of the initial adsorption capacity during the cycle. The adsorbent material not only exhibits high selectivity and excellent adsorption performance for heavy metal ions, but also has a simple and efficient preparation method.

[0025] Compared with the prior art, the present invention has the following significant advantages:

[0026] 1. The present invention introduces an innovative preparation method for producing a copolymerized polyacrylamide and acrylic acid hydrogel based on corn straw cellulose. The method uses cellulose to construct a skeleton, and through copolymerization modification of acrylic acid and acrylamide, the water absorption, water retention and mechanical strength of the hydrogel are significantly enhanced. In addition, the use of corn straw as a raw material not only improves the resource utilization of agricultural waste, but also realizes the efficient recycling of waste. The hydrogel can reach adsorption saturation within 2 hours, and the rapid adsorption rate is of great significance for rapid response and treatment of heavy metal contaminated water bodies.

[0027] 2. The hydrogel adsorption material of the present invention exhibits excellent adsorption performance when in contact with wastewater containing heavy metals. + 、Na + , Ca 2+ Mg 2+ ), it can maintain a high adsorption capacity, showing strong resistance to environmental interference. After six cycles of use, its adsorption efficiency remains stable, which proves its reliability and durability in practical applications.

[0028] 3. The preparation method of the present invention is simple and easy to operate, the operating conditions are easy to control, the raw materials are widely available, and the production process is green and environmentally friendly. These characteristics make the present invention have broad application prospects in the field of heavy metal wastewater treatment, and provide an efficient and sustainable solution for environmental protection and resource recycling. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 Corn straw cellulose CC (a), corn straw cellulose co-polyacrylamide acrylic acid hydrogel CC-P (AA-co-AM) (b, c), CC-P (AA-co-AM) hydrogel adsorption of Pb 2+ 、Cd 2+ , Cu 2+ SEM images after (df);

[0030] Figure 2 FTIR images of CC and CC-P (AA-co-AM) hydrogels;

[0031] Figure 3 CC-P(AA-co-AM) hydrogel and adsorption of Pb 2+ 、Cd 2+ , Cu 2+ XPS graph after

[0032] Figure 4 Competitive interference ions for the adsorption of Pb on CC-P(AA-co-AM) hydrogel 2+ 、Cd 2+ , Cu 2+ The influence diagram of DETAILED DESCRIPTION

[0033] Some embodiments of the present invention provide a method for preparing corn straw cellulose copolymerized with polyacrylamide and acrylic acid hydrogel, comprising the following steps:

[0034] (1) pre-treating the corn stalks by first boiling them in a sodium hydroxide solution and then bleaching them in a sodium hypochlorite solution. After the treatment, pure corn stalk cellulose is obtained by filtering, washing and drying;

[0035] (2) dissolving the pretreated corn stover cellulose in a sodium hydroxide / urea / water (alkaline urea) system to form a translucent cellulose solution, i.e., reaction system 1;

[0036] (3) mixing acrylic acid and acrylamide in water to form a uniform modified solution, i.e., reaction system 2;

[0037] (4) Slowly add reaction system 2 to reaction system 1 and stir thoroughly to ensure uniform mixing. Then, add N,N'-methylenebisacrylamide as a crosslinking agent and potassium persulfate as an initiator;

[0038] (5) heating the mixed solution obtained in step (4) in an oven to promote a gelation reaction, thereby forming a hydrogel;

[0039] (6) The hydrogel obtained in step (5) is thoroughly washed to remove unreacted monomers. Finally, the hydrogel is placed in an oven for drying to obtain the final cellulose copolymerization with acrylic acid and acrylamide hydrogel adsorption material, which is dried and stored.

[0040] In the present invention, optionally, the pretreatment in step (1) includes washing, drying and crushing in sequence. In the present invention, the washing agent is preferably water, and the number of washing times is based on effectively removing impurities on the surface of the corn stalks. The drying temperature is preferably 60°C, and the time is not limited until the material is completely dried. The rotation speed of the crushing is preferably 30000r / min, and the time is preferably 30s.

[0041] In the present invention, optionally, the mass volume ratio of the corn stalk to the sodium hydroxide solution and the sodium hypochlorite solution in step (1) is preferably 1: (15-20), the mass fraction of the sodium hydroxide solution is preferably 5-15%, more preferably 7%, the alkali boiling temperature is preferably 50-70° C., more preferably 60° C., and the alkali boiling time is preferably 2-3 hours. In the present invention, alkali boiling can remove organic macromolecules in the corn stalk, such as hemicellulose.

[0042] In the present invention, optionally, the mass concentration of the sodium hypochlorite solution in step (1) is preferably 5 to 15%, more preferably 8%, the bleaching temperature is preferably 50 to 70° C., and the alkali boiling time is preferably 2 to 3 hours.

[0043] In the present invention, after the bleaching in step (1), preferably, filtering and washing are further included; the filtration is preferably carried out in a Buchner funnel, and the washing is performed until the solution becomes colorless.

[0044] In the present invention, optionally, the mass ratio of sodium hydroxide / urea / water in step (2) is (5-7):(12-15):(78-83). When it is lower or higher than the limit value, it may cause the problem of incomplete dissolution of corn straw cellulose.

[0045] In the present invention, optionally, the dissolution step of the corn straw cellulose in the alkaline urea system in step (2) is: placing the sodium hydroxide / urea aqueous solution in a 0°C ice water bath, weighing 0.5-1.5g of corn straw cellulose and dispersing it into the alkaline urea solution, and stirring at a speed of 600-800r / min for 30-40min to obtain a translucent cellulose solution.

[0046] In the present invention, optionally, in step (3), the mass ratio of the acrylic acid to the aforementioned corn straw cellulose is 0.5 to 1:1, and the mass ratio of the acrylamide to the aforementioned corn straw cellulose is 1 to 2:1.

[0047] In the present invention, optionally, the volume ratio of the reaction system 1 to the reaction system 2 in step (4) is 1 to 5: 1. If the volume ratio is less than 1: 1, the adsorption performance of the hydrogel will be affected, and too low a dosage of corn straw cellulose will reduce the mechanical strength of the hydrogel and affect the cross-linking reaction; if the volume ratio is greater than 4: 1, the adsorption performance will also be affected to a certain extent, and too low a dosage of the modified solution will result in too few binding sites for heavy metal ion adsorption, which will affect the adsorption performance of the adsorption material.

[0048] In the present invention, optionally, the cross-linking agent in step (5) preferably includes N,N'-methylenebisacrylamide (MBA), and the initiator preferably includes potassium persulfate (KPS).

[0049] In the present invention, optionally, in step (5), the molar amount of the crosslinking agent is 1-2% of the molar amount of the total monomers (acrylic acid and acrylamide), and the molar amount of the initiator is 0.5-1% of the molar amount of the total monomers.

[0050] In the present invention, optionally, the polymerization reaction temperature in step (5) is 55-65°C, and the heating time is 2-3h. If the temperature is lower than 55°C, the cross-linking reaction is insufficient and insufficient for gelation; if the temperature is higher than 65°C, the morphology of the hydrogel will be affected.

[0051] In the present invention, optionally, the washing in step (6) includes water washing, and the water washing preferably includes distilled water; the present invention does not limit the number and amount of water washing, and it is only necessary to remove the unreacted monomers. The drying temperature is preferably 60°C, and there is no limit on the drying time, and it can be dried to constant weight.

[0052] The present invention also provides a corn straw cellulose copolymerized with polyacrylamide and acrylic acid hydrogel obtained by the above preparation method, such as Figure 1 As shown, it has a three-dimensional porous structure, a rough and uneven surface, a network distribution structure, a variety of functional groups, good water absorption and swelling performance, a swelling ratio of 170.4, and a good resistance to Pb 2+ 、Cd 2+ , Cu 2+ The maximum adsorption capacity of Pb was 434.8 mg / g, 277.7 mg / g, and 261.8 mg / g, respectively. After 6 cycles, the developed adsorption material showed good cycle stability, and its adsorption performance was hardly affected significantly. The specific results showed that after the sixth cycle, Pb 2+ The adsorption capacity of Cd decreased from 445 mg / g to 410 mg / g. 2+ The adsorption capacity of Cu 2+ The adsorption capacity slightly decreased from 150 mg / g to 135 mg / g. The above data show that the material still maintains about 90% of the initial adsorption capacity during the cycle.

[0053] The present invention also provides an application of the corn straw cellulose copolymerized with polyacrylamide acrylic acid hydrogel obtained by the above-mentioned preparation method in the adsorption of heavy metal ions.

[0054] In the present invention, optionally, the heavy metal ions include Pb 2+ 、Cd 2+ , Cu 2+ One or more of .

[0055] Example 1

[0056] 1. Extraction of corn straw cellulose

[0057] First, corn stover (WS) was thoroughly washed to remove impurities and then dried in an oven at 60 °C to remove moisture. The dried WS was placed in a grinder and ground at 30,000 r / min for 30 s to obtain fine powder. In order to remove hemicellulose, the obtained powder was alkali-boiled with 7 wt% sodium hydroxide solution at 60 °C for 2 h, and the solid-liquid ratio was maintained at 1:15. After the treatment, the material was washed several times with distilled water until the washing liquid reached neutrality. Then, the material was dried at 60 °C and crushed into powder. Subsequently, the powder was mixed with 8 wt% sodium hypochlorite solution in a ratio of 1:15 and stirred continuously at 65 °C for 2 h to remove lignin. After stirring, the material was filtered and repeatedly washed with distilled water until the pH value of the material reached neutrality. Finally, the washed material was dried in an oven at 60 °C, and the resulting product was corn stover cellulose (CC).

[0058] 2. Preparation of corn straw cellulose co-polyacrylamide acrylic acid hydrogel (CC-P(AA-co-AM))

[0059] Take 1g CC and evenly disperse it in 25g of an aqueous solution containing 7wt% NaOH and 12wt% urea. Place this mixture in an ice water bath at 0°C and stir at 700r / min for 30min to form a translucent viscous cellulose solution, namely reaction system 1. In another beaker, add 0.5ml AA and 1g AM to sufficient water and stir evenly until the total volume reaches 20mL to prepare a modified solution, namely reaction system 2. Slowly add reaction system 2 dropwise to reaction system 1 and continue stirring for 1 hour to ensure uniform mixing. In the formed homogeneous hydrogel precursor mixture, 50mg MBA as a crosslinker and 50mg APS as an initiator are added in sequence to start the polymerization reaction. The mixture is kept at 60°C for 3h to promote the completion of the chemical crosslinking reaction, thereby obtaining CC-P(AA-co-AM). After the reaction is completed, the hydrogel is rinsed with distilled water several times until its pH value reaches neutral. Subsequently, the hydrogel is dried at 60°C.

[0060] Application Example 1

[0061] Performance characterization test of the hydrogel adsorption material prepared in Example 1

[0062] (1) SEM analysis

[0063] Figure 1 SEM images of CC (a), CC-P (AA-co-AM) hydrogel (bc) and CC-P (AA-co-AM) hydrogel after adsorption of heavy metals (df).

[0064] Figure 1 The CC morphology in (a) exhibits a sheet-like structure with rough fibril segments. Figure 1 (bc) is the SEM image of CC-P(AA-co-AM) hydrogel after drying. The gel surface is very rough and has abundant pore structures. These characteristics help to increase the contact area between the adsorbent material and heavy metal ions. Figure 1 (df), it can be clearly seen that a large number of wrinkles appeared on the surface, indicating that the pore structure changed significantly during the adsorption process, which may be due to the compression of the pore structure caused by the filling effect of heavy metal ions.

[0065] (2) FTIR analysis

[0066] FTIR was used to analyze the functional group types of CC-P(AA-co-AM) hydrogels.

[0067] like Figure 2 As shown in the figure, the CC-P(AA-co-AM) hydrogel has the characteristic peak of CC and an additional peak at 2930 cm -1 , 3353cm-1, 3207cm-1 and 1456cm-1 correspond to the single bond -OH stretching of AA, -OH groups present in cellulose and acrylate components, and -COOH, respectively. Different peaks are shown at 1663cm-1, 1544cm-1, 1160cm-1 and 1057cm-1, corresponding to amide I, C=O, -CH2 and CN bonds, respectively.

[0068] (3) XPS analysis

[0069] XPS was used to analyze the elemental composition of CC-P(AA-co-AM) hydrogel and after adsorption.

[0070] like Figure 3 As shown in the figure, the hydrogel mainly contains C, N, O, and Na elements. After adsorbing heavy metal ions, peaks corresponding to Pb4f, Cd3d, and Cu2p appear. The disappearance of the Na1s peak indicates that an ion exchange reaction occurs between -COONa groups. 5 / 2 (143eV) and Pb4f 7 / 2 The peak at (138.3 eV) shows the formation of complexes on the gel, such as -OH-Pb, -O-Pb or -CO-Pb. The high-resolution spectrum of Cd3d shows that Cd3d 5 / 2 (404.97eV, 405.53eV, 406.12eV) and Cd3d 3 / 2 The peaks at (411.73 eV, 412.26 eV, and 412.85 eV) correspond to -OH-Cd and -CO-Cd, respectively. The binding energies of these peaks are different from those of the ionic forms, indicating that Cd 2+ It is not attached to the adsorbent material in the form of ions, but in the form of coordination compounds. In the spectrum of Cu2p, Cu2p 5 / 2 and Cu2p 3 / 2 The peaks are attributed to the presence of Cu-O, Cu(OH)2 and -COO-Cu.

[0071] Adsorption performance test of CC-P (AA-co-AM) hydrogel prepared in Example 1

[0072] Pre-configured with 1g / L Pb 2+ 、Cd 2+ , Cu 2+The stock solution of the metal solution with different concentrations used in the experiment was diluted with the stock solution, and the pH value was adjusted by dropping 0.1mol / L HNO3 or 0.1mol / L NaOH solution. The temperature was set to 298K, the speed was 160r / min, and three parallel tests were set for each performance test.

[0073] (1) Effect of pH on adsorption

[0074] Weigh 0.02 g CC-P(AA-co-AM) and put it into a beaker. The beaker was filled with 100 mL 100 mg / L Pb 2+ 、Cd 2+ , Cu 2+ The pH value of the solution was adjusted to 2, 3, 4, 5, and 6 respectively, and the solution was placed in a constant temperature water bath shaker for 2 hours. After the adsorption was completed, the supernatant was filtered through a 0.45 μm filter membrane and the residual concentration was determined by a flame atomic absorption spectrometer to calculate the adsorption amount.

[0075] CC-P(AA-co-AM) hydrogels have a strong affinity for Pb in the pH range of 2 to 6. 2+ 、Cd 2+ and Cu 2+ All of them showed good adsorption effect. Under the strong acidic condition of pH 2, the adsorption amount was relatively low, which may be due to the H + The limited adsorption sites compete with heavy metal ions, and the swelling capacity of the hydrogel is reduced, which limits the diffusion of heavy metal ions inside the hydrogel. However, when the pH value is increased to 3 or higher, the adsorption efficiency of CC-P (AA-co-AM) hydrogel for the above heavy metal ions is significantly improved, which may be due to the reduction of repulsion between the surface of the adsorbent material and the pollutants at higher pH values. At a pH of 5, the hydrogel exhibits the best adsorption performance, so subsequent experiments were carried out under this optimal pH condition.

[0076] (2) Cyclic adsorption test

[0077] Mix 50mL of 200mg / L heavy metal ion solution with 10mg CC-P(AA-co-AM) hydrogel. Adsorb to equilibrium under optimal pH conditions. Remove the hydrogel particles from the solution and rinse them three times with deionized water. Stir the hydrogel particles in 0.5M HNO3 solution for 2h, and then treat them with 0.01M NaOH for 8h to extract the adsorbed heavy metal ions from the hydrogel. The adsorption-desorption process was repeated 6 times. After 6 cycles, the developed adsorbent material showed good cyclic stability, and its adsorption performance was hardly significantly affected. Specific results showed that after the sixth cycle, Pb 2+ The adsorption capacity of Cd decreased from 445 mg / g to 410 mg / g.2+ The adsorption capacity of Cu 2+ The adsorption capacity slightly decreased from 150 mg / g to 135 mg / g. The above data show that the material still maintains about 90% of the initial adsorption capacity during the cycle, and the attenuation of the adsorption capacity is small. Even after multiple uses, the gel maintains a good removal rate for heavy metals.

[0078] (3) Effect of interfering ions on adsorption

[0079] Select different initial concentrations of Na + , K + , Ca 2+ and Mg 2+ As an interfering ion, Pb 2+ 、Cd 2+ , Cu 2+ The concentration is 100 mg / L, take 100 mL, the amount of adsorption material is 20 mg, and place it in a constant temperature water bath shaker for 4 hours. Take the supernatant and filter it through a 0.45 μm filter membrane, and then use a flame atomic absorption spectrometer to determine the residual concentration and calculate the adsorption amount.

[0080] The results are as follows Figure 4 As shown, 0.01M Na + or K + After that, Pb 2+ 、Cd 2+ and Cu 2+ The adsorption performance of Pb 2+ The adsorption capacity of Cd decreased slightly from 441 mg / g to 432 mg / g or 436 mg / g; 2+ The adsorption capacity of Cu 2+ The adsorption capacity of Pb decreased slightly from 148 mg / g to 145 mg / g or 144 mg / g. Relatively speaking, when the concentration of these interfering ions increased to 0.1 M, the adsorption efficiency decreased significantly, among which Pb 2+ The adsorption capacity of Cd was reduced to 415mg / g or 407mg / g; 2+ The adsorption capacity of Cu 2+ The adsorption capacity of Mg / g was reduced to 134 mg / g or 136 mg / g. This phenomenon can be attributed to the competition between interfering ions and heavy metal ions for limited adsorption sites, resulting in a decrease in the effective availability of active groups on the hydrogel, which in turn affects its adsorption capacity for heavy metal ions. In particular, Mg 2+ and Ca 2+ The effect on adsorption efficiency is more significant, and the order of influence is Ca 2+ >Mg2+ >Na + >K + , which is related to the electronegativity and valence of the interfering ions. Experimental data show that divalent cations have a more significant interference effect on adsorption efficiency than monovalent cations.

[0081] The above description is only a preferred example of the present invention and does not limit the present invention in any way. Without departing from the principle of the present invention, any simple modification to the embodiment is made and all such modifications fall within the scope of the technical solution of the present invention.

Claims

1. The present invention relates to a method for preparing a hydrogel adsorption material of corn straw cellulose-based copolymerized polyacrylamide and acrylic acid, the steps of which are as follows: S1, pre-treating corn stalks by firstly performing alkaline boiling treatment in a sodium hydroxide solution and then performing bleaching treatment in a sodium hypochlorite solution; after the treatment is completed, obtaining pure corn stalk cellulose through filtering, washing and drying steps; S2, dissolving the pretreated cellulose in a sodium hydroxide / urea / water system to form a translucent solution, i.e., reaction system 1; S3, mixing acrylic acid and acrylamide in water to form a uniform modified solution, i.e., reaction system 2; S4, slowly adding reaction system 2 into reaction system 1, and stirring thoroughly to ensure uniform mixing; Then, N,N'-methylenebisacrylamide was added as a cross-linking agent and potassium persulfate as an initiator; S5, heating the mixed solution obtained in step S4 in an oven to promote a gelation reaction, thereby forming a hydrogel; S6, washing the hydrogel obtained in step S5 thoroughly to remove all unreacted monomers; finally, drying the hydrogel in an oven to obtain a final hydrogel adsorption material product, which is then dried and stored.

2. In the preparation method described in claim 1, the pretreatment of step (1) further includes washing, drying and crushing in sequence; water is preferably used as a reagent in the washing process, and the number of washing times is based on effectively removing impurities on the surface of the corn stalks; the drying process is carried out at a temperature of 60°C to 70°C until the material is completely dry; the rotation speed of the crushing process is preferably 30,000 r / min, and the duration is 30 to 60 s.

3. In the preparation method described in claim 1, in step (1), the mass volume ratio of corn stalks to sodium hydroxide solution and sodium hypochlorite solution is preferably 1: (15-20); the mass fractions of the sodium hydroxide and sodium hypochlorite aqueous solutions are 5-15% respectively; the heating temperature should be controlled at 50° C. to 70° C., and the heating time is maintained at 2-4 hours.

4. In the preparation method described in claim 1, the mass ratio of sodium hydroxide / urea / water in step (2) is (5-7):(12-15):(78-83); the method for dissolving corn straw cellulose in system 1 is: placing the sodium hydroxide / urea / water solution in a 0°C ice water bath, weighing 0.5-1.5g of cellulose and rapidly dispersing it into the solution, and rapidly stirring at a speed of 600-800r / min for 30-40min to obtain a translucent cellulose solution.

5. In the preparation method according to claim 1, in step (3), the mass ratio of acrylic acid to corn straw cellulose is 0.5 to 1:1, and the mass ratio of acrylamide to corn straw cellulose is 1 to 4:

1.

6. In the preparation method according to claim 1, in step (4), the volume ratio of reaction system 1 to reaction system 2 is 1-5:1; the molar amount of the crosslinking agent is 1-2% of the molar amount of the total monomers (acrylic acid and acrylamide), and the molar amount of the initiator is 0.5-1% of the molar amount of the total monomers.

7. In the preparation method according to claim 1, the heating temperature in step (5) is 50-60°C and the heating time is 2-3h.

8. In the preparation method described in claim 1, the drying temperature in step (6) is 60-70°C, and the drying time is not limited until the hydrogel reaches a constant weight.

9. A corn straw cellulose copolymerized with polyacrylamide and acrylic acid hydrogel adsorbent prepared by any one of the methods of claims 1 to 8, characterized in that It has a three-dimensional porous structure and excellent water absorption and swelling performance, with a swelling ratio of up to 170.4; the adsorbent contains hydroxyl (-OH), carboxyl (-COOH), carbonyl (C=O) and carbon-nitrogen bond (CN), and has good water absorption and swelling performance for lead (Pb 2+ ), cadmium (Cd 2 + ), copper (Cu 2+ ) ions showed significant adsorption capacity, and the maximum adsorption amounts were 434.8 mg / g, 277.7 mg / g, and 261.8 mg / g, respectively.

Citation Information

Cited By

  • Preparation method of aluminum silicate nanofiber / acrylamide-sodium acrylate copolymer composite aerogel

    CN119455919A

  • Lignocellulose modified ammonium polyphosphate hydrogel slow release fertilizer and preparation method thereof

    CN119462271A

  • A kind of lignocellulose modified ammonium polyphosphate hydrogel slow-release fertilizer and preparation method thereof

    CN119462271B

  • Water-retaining phosphorus-absorbing hydrogel as well as preparation method and application thereof

    CN120205108A

  • Multi-core organic-inorganic composite flocculant as well as preparation method and application thereof

    CN120423662A